2009
DOI: 10.1021/ac900045m
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Lipidomic Analysis of Nonalcoholic Fatty Liver by Cluster TOF-SIMS Imaging

Abstract: Mass spectrometry imaging has been used to map liver biopsies of several patients suffering from nonalcoholic fatty liver disease. This steatosis is characterized by an accumulation of triacylglycerols and diacylglycerols in the liver. Using time-of-flight-secondary ion mass spectrometry (TOF-SIMS) with a bismuth cluster ion source, it has been possible to map lipids in situ at the micrometer scale and to simultaneously characterize their molecular distribution on liver sections. Accumulation of triacylglycero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 38 publications
7
121
0
2
Order By: Relevance
“…There are few other lipidomic studies on assessment of NAFLD. By Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS) imaging in thin sections of steatotic livers from patients, main DG and TG species were detected similar to our LC-MS/MS data ( 34 ). Based on a lipidomic approach and a mouse model similar to ours, it was reported that steatotic liver contains particularly enhanced metabolically linked DG and PC species ( 7 ).…”
Section: Discussionsupporting
confidence: 79%
“…There are few other lipidomic studies on assessment of NAFLD. By Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS) imaging in thin sections of steatotic livers from patients, main DG and TG species were detected similar to our LC-MS/MS data ( 34 ). Based on a lipidomic approach and a mouse model similar to ours, it was reported that steatotic liver contains particularly enhanced metabolically linked DG and PC species ( 7 ).…”
Section: Discussionsupporting
confidence: 79%
“…This technique has already been used to image tocopherol location in cells [102] and tissues [103][104][105]. It would be fascinating if someone should now apply the tools of lipidomics to collecting data not only on the location of tocopherol, but also the phospholipid profile at the same location.…”
Section: Is All Of This Relevant For Understanding the Biological Actmentioning
confidence: 99%
“…This method now enables drawing from various kinds of samples the density map (image) of any ion present in the mass spectra, with a spatial resolution from a few m to less than 500 nm, and with a mass range which is now reaching more than 1000 Da. In recent years, many applications of TOF-SIMS imaging have been published in the fields of biology and medicine [32][33][34][35][36][37][38][39][40][41][42][43]. However, it has never been directly applied to the exploration of persistent organic pollutants such as environmental or food contaminants.…”
mentioning
confidence: 99%